12-Year Outcomes of Microkeratome-Assisted Anterior Lamellar Therapeutic Keratoplasty (ALTK) for Disorders of the Anterior Part of the Corneal Stroma – A Comparative Review of Adult and Children - Guber, Ivo; Bergin, Ciara; Othenin-Girard, Philippe; Munier, Francis; Majo, François (Klinische Monatsblätter für Augenheilkunde, 2018)
Purpose To report the visual outcomes and complications of automated anterior lamellar therapeutic keratoplasty (ALTK) in adults and children, and to examine these outcomes as a function of age and etiology.Methods A consecutive series of cases undergoing automated ALTK procedures performed at the Jules-Gonin Eye Hospital Lausanne, Switzerland, between June 2003 and January 2015. Only patients with at least 3 months of follow-up were included.Results There were 53 eyes (24 right) of 51 patients (17 female, 16 juvenile), with a mean age of 34.8 years (range from 3 months to 88 years), analyzed. The mean follow-up was 35 (± 26) months. Diagnosis in the adult (n = 37) vs. juvenile (n = 16) eyes was different: opacity following surgical complication 8 vs. 0, congenital 1 vs. 1, dystrophy 5 vs. 2, infection 12 vs. 5, keratectasia 3 vs. 0, trauma 7 vs. 0, tumor 1 vs. 3, and allergy 0 vs. 5. Visual impairment as a consequence of corneal scarring was the principle indication for surgery in both adult (70%; 26) and juvenile eyes (63%; 10); other indications were choristoma, dermoid, other tumors, astigmatism, and congenital opacity. In adult vs. juvenile eyes, the mean visual acuity (spectacle and contact lenses) was, at last visit, 0.55 vs. 0.45 LogMAR (p = 0.78), with a range of 100% to hand movements. Failure occurred in 6 (16%) vs. 2 (13%) cases and complications were observed in 14 (38%) vs. 9 (56%) cases, however, more surgical revision was required in juvenile eyes, 4 (11%) vs. 7 (43%) (p = 0.01, Fisher test).Conclusions This study shows that anterior lamellar keratoplasty in children retains good visual function when combined with adequate amblyopic therapy. However, the rate of complications is higher in juveniles and requires more intensive interdisciplinary follow-up.
Keywords: cornea; corneal graft; lamellar keratoplasty; anterior lamellar keratoplasty; microkeratome